Peluang dan Tantangan Pengembangan Usaha Mikro Kecil Menengah (UMKM) Dari Berbagai Aspek Ekonomi - Maulida Sri; Yunani Ahmad (Universitas Pendidikan Nasional, 2017)
This research aims to discuss the opportunities and challenges of the sharia financial aspects and digital marketing as a driving force for the development of Micro Small Medium Enterprises (MSMEs). This research uses descriptive explorative approach and developed by using literature review approach or literature study. The theory or conceptual approach is done by referring from several sources, such as books, scientific journals, and the internet. All existing ideas are combined in a single frame of thought. The results show that the development of digital technology and the shari’a finance is increasing rapidly, in addition to being a challenge for the business world has also become a great opportunities and potential for economic and business improvement. Businesses must be able to follow the changing trend by utilizing information technology to drive business activities and increase competitiveness. Businesses must be able to create change and new innovations in the company that are able to create opportunities and new markets by utilizing information technology and the development of digital convergence in the community. On the other hand, MSMEs can be encouraged by some policies either from the government or the business peoples of MSMEs by utilizing the traditional community structure and Shari'ah Micro Finance Institution (BMT), product design and innovation, strengthening human resources, Policy on MSMEs Products, Exhibition and Maximizing the Role of Women and maximize the implementation of MSMEs policies. Keywords: MSMEs, Shari’a Financial Institution, Digitial Marketing